AKTIVITAS DAN SUMBER PENDAPATAN PETANI MISKIN BERLAHAN SEMPIT DI DAERAH SAWAH TADAH HUJAN DATARAN RENDAH (Kasus: Dua Desa di Kabupaten Bojonegoro ) - VALERIANA DARWIS; A. ROZANY NURMANAF (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id)
There were several criteria that stick on a poor family, which are law educational level, thebiggest proportion of their income from the farming activity and the small farm landownership. Commonly the poor farm household in the study location owned a plot of rainfedand a plot of upland which avarage about 0.279 ha and 0.2 ha. The cropping patern on rainfedwas rice and secondary crops was tobacco. By existing planted area their minimal livingrequirement mostly couldn’t be fulfilled and needed other sources. Income from farmingactivity in the last year was 42.77 percent and the other 57.23 percent came from nonagricultural sector. Although allocated time was greater in farming activity, however theincome was lower than from non agricultural https://www.budidayatani.com. To alleviate poverty mainly of those smallscale farmer, an increasing water resourse was required in order to increase land productivity.Besides, quidance of farming technology practices and support were require sector.